KEBERADAAN POPULASI KOLONI Apis dorsata Fabr. AGREGASI (HYMENOPTERA: APIDAE) DI SIJUNJUNG - Handriani, Elida; Jasmi, Jasmi; Indriati, Gustina (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Apis dorsata bees are social insect, which in a normal colony consists of caste is a queen several hundread males and several thousand workers. Hive of honey Apis dorsata bees contains eggs, larva, pupa, pollen, honey and sometimes water. In connection with that have done research on the existence of colonies Apis dorsata Fabr. Agregation population(Hymenotera: Apidae) in Sijunjung. April â June 2013 with the aim to determine the existence of population colonies Apis dorsata Fabr. Agregation in Sijunjung. This study uses a descriptive survey methos by observing colonie of Apis dorsata Fabr. Agregation directly of the kapok tree is by counting the number of active colonies, colonies are moved and the relationship of physical environment factors. The results of research is got the number of active colonies that is at most 14 active colonies and at 3 colonies. Where the number af active colonies are most commonly found on branches 1-2 and on the twigs 1-2 while the number at least on branches 9-10, and number of colonies that move is 7 colonies were found on branches 1- 2. Number of colonies that are mostly foundÂ in April, while the at least in June. Nesting trees that are in Palangki 1 m and Pasar Jumâat 30 cm.Â